Relationship between neck muscle activation and head-neck response in low velocity frontal collision - Kak, D-Wing (2016)
Neck injury is not a rare occasion in car crash accident. Occurrence of neck injuries due to car crash accident has increased 11 times within 20 years in Netherlands. Road Safety Research Center (RSRC) of UPM reported that 60% of all neck injuries resulted to fatality of motorcyclist in road collision at Malaysia. High expenses are spent on medical, insurance and hospitality on neck injury related to car crash annually. Proper countermeasure has to be taken to mitigate the occurrence of neck injury in crash. Previous study has proven that neck active muscle is capable to generate force to reduce 30-35% of head rotations and head angular velocities in rear-end collision. Thus, it is critical to understand the behavior of neck muscle responses before a biofidelity head-neck mathematical model can be designed. Nevertheless, the behavior of neck active muscle response under static and dynamic loading is still yet to be established. This study aims to establish relationship between neck muscle response and head-neck response in low speed collision through experimental test. In this study, there are two main experimental test which are static neck muscle strength test and low velocity frontal collision test. Neck muscle sternocleidomastoid and semispinalis capitis which are primary neck flexor and extensor are selected to be studied in this study. In static neck strength test, the measured maximum neck muscle strength is 64.5 N and 96.7 N for flexion and extension. This study has established models to relate neck muscle EMG activity and neck muscle force for neck flexor and extensor muscles. This model can explain 82.9%-85.4% of the data variables with a negative quadratic relationship. The neck muscle force generated at the same activation level is different between static and dynamic loading condition. In low velocity collision test, the peak linear head accelerations are 4.61G and 7.35G relative to torso for impact speed of 2.17 m/s and 2.47 m/s respectively. An empirical model has established to relate neck muscle activation level based on head linear acceleration and angular acceleration where R2= 0.934. Neck extensor, semispinalis capitis are the dominant muscle with high level of activation level in low velocity frontal collision test. On the hand, neck flexor, sternocleidomastoid only activated at about 30-40% in the collision tests. The established empirical models can be applied to relate neck muscle activation level and muscle force in low velocity frontal collision. This can further enhance accuracy and precision of current head-neck simulation model in simulating kinematic response of human head in crash